1976
DOI: 10.1056/nejm197608052950602
|View full text |Cite
|
Sign up to set email alerts
|

The Resistance Factor toPlasmodium vivaxin Blacks

Abstract: Duffy-blood-group-negative human erythrocytes, FyFy, are resistant to invasion in vitro by Plasmodium knowlesi. The FyFy genotype is found predominantly in African and American blacks, who are the only groups completely resistant to infection by P. vivax. To determine if the FyFy genotype is the vivax resistance factor, we performed blood typing on 11 black and six white volunteers who had been exposed to the bites of P. vivax-infected mosquitoes. Only the five FyFy blacks were resistant to erythrocytic infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
749
1
25

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,170 publications
(813 citation statements)
references
References 10 publications
14
749
1
25
Order By: Relevance
“…Moreover, mixed infections are either randomly distributed [31,32] or there might be a short age of LM-detected mixed infections [28]. Apart from differences in a wide range of ecological factors (such as climate and Anopheline vector species), these contrasting observations in P. malariae epidemiology could be linked to the virtual absence of Plasmodium vivax infections in many African populations because of the lack of the Duffy blood-group-antigen, which P. vivax requires to invade red blood cells [33]. Interestingly, Smith et al reported that in Wosera, PNG, P. vivax infections might be associated with an antagonistic effect on P. malariae infections [34].…”
Section: Variation In Parasite Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mixed infections are either randomly distributed [31,32] or there might be a short age of LM-detected mixed infections [28]. Apart from differences in a wide range of ecological factors (such as climate and Anopheline vector species), these contrasting observations in P. malariae epidemiology could be linked to the virtual absence of Plasmodium vivax infections in many African populations because of the lack of the Duffy blood-group-antigen, which P. vivax requires to invade red blood cells [33]. Interestingly, Smith et al reported that in Wosera, PNG, P. vivax infections might be associated with an antagonistic effect on P. malariae infections [34].…”
Section: Variation In Parasite Prevalencementioning
confidence: 99%
“…However, the fact that P. ovale has been found to be most prevalent in areas of West Africa, where P. vivax is almost absent because of the high prevalence of the Duffy blood-group-negative phenotype [33], might also indicate a negative interaction between these two species. Because P. ovale prevalence and parasitemia are consistently low, it is often the case that there are insufficient observations to enable meaningful statistical evaluations regarding interactions between P. ovale and the other malaria parasite species that infect humans.…”
Section: Why Are P Malariae and P Ovale Infections Still Important?mentioning
confidence: 99%
“…Human erythrocytes lacking the Duffy antigen are not invaded by P. knowlesi merozoites, and invasion can be blocked with anti-Duffy antibodies. Humans lacking the Duffy blood group antigens are also resistant to infection by Plasmodium vivax, a human malaria, indicating that this malaria also requires the Duffy antigen as a ligand for invasion [3]. Due to this requirement, P. vivax is absent from West Africa where almost all of the population is Duffy negative.…”
mentioning
confidence: 99%
“…Duffy binding protein (DBP), the first such ligand identified in micronemes of invasive malaria merozoites [2], is absolutely vital for the invasion process of Plasmodium vivax [3]. Cysteine-rich region II of the DBP comprises the prototypical Duffy binding like (DBL) ligand domain [4,5], which is also found in other erythrocyte binding proteins (EBA-175, BAEBL, JESEBL) and in cytoadherence proteins (PfEMP-1) [6].…”
Section: Plasmodium Merozoite Invasion Is a Multi-step Processmentioning
confidence: 99%